The Enigma of Low COVID-19 Fatality Rate in India - Samaddar, Arghadip; Gadepalli, Ravisekhar; Nag, Vijaya Lakshmi; Misra, Sanjeev (Frontiers in Genetics, 2020)
COVID-19 is an acute onset pneumonia caused by SARS-CoV-2 which has rapidly evolved into a pandemic. Global statistics have shown a considerable variation in COVID-19 fatality rates with a striking difference observed in the figures from India. As of July 3, 2020, India has reported a case positivity rate of 6.5% and a fatality rate of 2.8% which are among the lowest in the world. Also, the severity of the disease is much less among Indians as evidenced by the low rate of ICU admission (15.3%) and the need for mechanical ventilation (4.16%). As per the World Health Organisation (WHO) situation report 165 on July 3, 2020, India has one of the lowest deaths per 100,000 population (1.32 deaths against a global average of 6.04). Several factors related to the pathogen, host and environment might be responsible for lowering the susceptibility of Indians to COVID-19. These include mutations in SARS-CoV-2 strains, host factors like innate immunity, genetic diversity in immune responses, epigenetic factors, polymorphisms of ACE2 receptors, micro RNAs and BCG vaccination, and environmental factors like high temperature which may alter the viability and transmissibility of the strain. This perspective highlights the potential factors that might be responsible for the observed low COVID-19 fatality rate in Indian population. It puts forward several hypotheses which can be a ground for future studies determining individual and population susceptibility to COVID-19 and thus, may offer a new dimension to our current understanding of the disease.